(untitled) (American Journal of Medical Science and Innovation, 2023)
Several studies have established region-based prevalence rate of H. pylori infection and its association with clinical outcomes in Bhutan. However, this study attempts to determine hospital-based prevalence rate of H. pylori and its association with clinical outcomes. A total of 347 volunteers (159 females and 188 males; mean age of 49.8 ± 15.5 years) were enrolled from Central Regional Referral Hospital (CRRH) in Gelephu. Upper gastro-intestinal endoscopy (UGIE) was performed among the dyspeptics and H. pylori infection was determined by Histology examination. The histological prevalence of H. pylori among 347 patients who went upper gastro-intestinal endoscopy was 55.6%. The prevalence of H. pylori infection increased with age but it was statistically insignificant (P > 0.05). Gastritis was the most common endoscopic finding, present in 309 (89%) patients followed by normal upper endoscopy results in 24 (6.9%) patients. The prevalence of H. pylori among patients with gastritis and a duodenal ulcer was significantly higher than in patients with gastric cancer (P < 0.05). The high incidence of gastritis in the hospital may be attributed to the high prevalence of H. pylori infection among the individuals with dyspepsia.